CO2 discharge from the bottom of volcanic Lake Rotomahana, New Zealand. (17th March 2014) - Mazot, Agnes; Schwandner, Florian M.; Christenson, Bruce; de, Cornel E. J.; Inguaggiato, Salvatore; Scott, Brad; Graham, Duncan; Britten, Karen; Keeman, J.; Tan, Karine
<x xml:space="preserve">Abstract</x> [1] From April 2010 to February 2011, CO2 flux surveys were performed on Lake Rotomahana, New Zealand. The area has been hydrothermally active with fumaroles and sublacustrine hydrothermal activity before and since the eruption of Mt Tarawera in 1886. The total CO2 emission from the lake calculated by sequential Gaussian simulation is 549 ± 72 t d−1. Two different mechanisms of degassing, diffusion through the water‐air interface and bubbling, are distinguished using a graphical statistical approach. The carbon dioxide budget calculated for the lake confirms that the main source of CO2 to the atmosphere is by diffusion covering 94.5% of the lake area (mean CO2 flux 25 g m−2 d−1) and to a lesser extent, bubbling (mean CO2 flux 1297 g m−2 d−1). Mapping of the CO2 flux over the entire lake, including over lake floor vents detected during the survey, correlates with eruption craters formed during the 1886 eruption. These surveys also follow regional tectonic patterns present in the southeastern sector of Lake Rotomahana suggesting a deep magmatic source (∼10 km) for CO2 and different pathways for the gas to escape to the surface. The values of δ13CCO2 (−2.88 and −2.39‰) confirm the magmatic origin of CO2.